The new real: media and mimesis in Japan from stereographs to Emoji - Abel, Jonathan E. (University of Minnesota Press, 2022)
Unlocking a vital understanding of how literary studies and media studies overlap and are bound together A synthetic history of new media reception in modern and contemporary Japan, The New Real positions mimesis at the heart of the media concept. Considering both mimicry and representation as the core functions of mediation and remediation, Jonathan E. Abel offers a new model for media studies while explaining the deep and ongoing imbrication of Japan in the history of new media.From stereoscopy in the late nineteenth century to emoji at the dawn of the twenty-first, Abel presents a pioneering history of new media reception in Japan across the analog and digital divide. He argues that there are two realities created by new media: one marketed to us through advertising that proclaims better, faster, and higher-resolution connections to the real; and the other experienced by users whose daily lives and behaviors are subtly transformed by the presence and penetration of the content carried through new media. Intervening in contemporary conversations about virtuality, copyright, copycat violence, and social media, each chapter unfolds with a focus on a single medium or technology, including 3D photographs, the phonograph, television, videogames, and emoji.By highlighting the tendency of the mediated to copy the world and the world to copy the mediated, The New Real provides a new path for analysis of media, culture, and their function in the world